The variability of strength production capacities during a judo contest - Serrano Huete, Victor; Latorre Román, Pedro Ángel; García Pinillos, Felipe; Morcillo Losa, José A.; Jiménez Reyes, Pedro; Párraga-Montilla, Juan A. (Physical Activity Revie, 2023)
Background. The muscular response of athletes in a judo contest is one of the most important aspect to measure with precision. Objective. Our purpose was to obtain and analyse the variability of strength associated to muscular performance parameters during a judo contest. Methods. Thirty-five men performed five 5-minute bouts with 15 minutes of passive rest. Immediately after each bout, muscular performance parameters were tested: countermovement jump (CMJ), maximal dynamic strength capacities (mean power velocity (MPV), mean strength (MS), maximum strength (MXS), mean power (MP) and maximum power (MXP)) in upper body, dominant (DHS) and non-dominant handgrip isometric strength (NDHS). ANOVA to compare baseline test data and successive bouts was used. Results. ANOVA revealed significant differences in NDHS (p<0.001), DHS (p<0.001), CMJ (p<0.001), MPV (p<0.001), MXS (p<0.001), MP (p<0.001) and MXP (p<0.001). No significant differences in MS (p = 0.008) were found. Some significant correlations between NDHS and ΔPMX (r=0.368, p=0.050), MPV and ΔMXS (r=0.528, p=0.001) and ΔMXP (r=0.683, p<0.001), MPX and ΔMXS (r=0.528, p=0.001) and ΔMP (r=0.877, p<0.001) were found. Conclusion. Due to judo contest can be considered a high intensity exercise, it produces an amount of muscular fatigue and therefore significant loss strength that it cannot be recovery during rest-times between successive bouts. For this reason, it was a high variability in strength production capacities, which are modified during a judo contest.
Keywords: judo contest; muscular fatigue; muscular performance parameters; strength; strength variability; Emerging; Scopus